ON INFLUENCE OF GEOMETRY OF MICROELECTROSOUNDING FIELD-ARRAYS ON THE MEASURING ACCURANCY FOR GEOECOLOGICAL INVESTIGATION - REVA, M.; ONYSHCHUK, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The result of calculations of the geometric parameters influence of the microelectrosounding and recommendations for their optimal sizes.